Penyisihan BOD, COD, TSS, dan TDS Menggunakan Adsorben Lumpur Lapindo dan Cangkang Kerang Darah pada Limbah Tekstil Jetis Sidoarjo - permatasari, tasya; rahmayanti, ardhana; rahman, annur; ruhaini; arifuddin, maulana rizki; firmansyah, achmad danial; afkar, khilyatul; Sumiyarsono, Elmi (2477 - 6165, 2023)
Jetis Batik Village is a Sidoarjo batik center that produces typical Sidoarjo handwritten batik. The batik processing process produces textile waste which must be processed before being discharged into the environment. Many producers, both large and household scale, have one thing in common, namely producing liquid waste, containing dyes, suspended solids, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Total Dissolved Solids (TDS) that need to be managed before being discharged into water bodies. One way of processing that can be done is by using adsorbents. Lapindo mud and Blood Clam shells are abundant natural materials that can be used to process textile waste. Varying adsorbent mass ratios were carried out to determine the optimal adsorbent ratio for processing textile waste. Variations in mass of Blood Clamshells and Lapindo mud (1:0, 0:1, 1:1, 1:2, 2:1). The best variation in reducing COD was variation C (1 g Lapindo mud and 1 g Blood Clam shell) with a removal efficiency of 89.13%. The best variation in reducing TDS is variation E (2 g Lapindo mud and 1 g Blood Clam shell) with an efficiency of 86.07%. The TSS removal efficiency showed relatively the same results 33.33%.